Longphongtook – an Indigenous Tribal Fishing Technique in Fast Flowing Rivers of Arunachal Pradesh, India - Dutta, R.; Bhagabati, S. K.; Mili, K.; Bhuyan, P. C.; Kumar, A.; Songtheng, P.; Borah, S. (Fishery Technology, 2019)
Longphongtook an indigenous fish aggregating methodpractised along the Namsang stream by Nocte tribeof Tirap district of Arunachal Pradesh has beendescribed in the present study. In this practice, fisheswere caught by attracting them to a circularstructure (diameter 2.5 to 2.75 m) made up ofboulders and pebbles of the river bed. The studyrevealed that thigmotropism behaviour of fish waseffectively and efficiently utilised by the fisher folkin this fishing technique. The catch mostly comprisedof migratory hill stream fishes.